Default mode network modifications in Fabry disease: A resting‐state fMRI study with structural correlations. Issue 4 (9th January 2018) - Cocozza, Sirio; Pontillo, Giuseppe; Quarantelli, Mario; Saccà, Francesco; Riccio, Eleonora; Costabile, Teresa; Olivo, Gaia; Brescia Morra, Vincenzo; Pisani, Antonio; Brunetti, Arturo; Tedeschi, Enrico; ,
Abstract: Aim of the study was to evaluate the presence of Default Mode Network (DMN) modifications in Fabry Disease (FD), and their possible correlations with structural alterations and neuropsychological scores. Thirty‐two FD patients with a genetically confirmed diagnosis of classical FD (12 males, mean age 43.3 ± 12.2) were enrolled, along with 35 healthy controls (HC) of comparable age and sex (14 males, mean age 42.1 ± 14.5). Resting‐State fMRI data were analyzed using a seed‐based approach, with six different seeds sampling the main hubs of the DMN. Structural modifications were assessed by means of Voxel‐Based Morphometry (VBM) and Tract‐Based Spatial Statistics analyses. Between‐group differences and correlations with neuropsychological variables were probed voxelwise over the whole brain. Possible correlations between FC modifications and global measures of microstructural alteration were also tested in FD patients with a partial correlation analysis. In the FD group, clusters of increased functional connectivity involving both supratentorial and infratentorial regions emerged, partially correlated to the widespread white matter (WM) damage found in these patients. No gray matter volume differences were found at VBM between the two groups. The connectivity between right inferior frontal gyrus and precuneus was significantly correlated with the Corsi block‐tapping test results ( p  = .0001). Widespread DMN changes are present in FD patients that correlate with WM alterations and cognitive performance. Our results confirm the current view of a cerebral involvement in FD patients not simply associated to major cerebrovascular events, but also related to significant and diffuse microstructural and functional changes.